Black carp NAP1 positively regulates MDA5-mediated antiviral signaling during the innate immune activation. (June 2020) - Cai, Can; Liu, Ji; Tan, Yaqi; Wei, Jing; Yang, Xiao; Xiao, Jun; Feng, Hao
Abstract: NAK-associated protein 1 (NAP1) is involved in NF-κB activation and interferon (IFN) induction in human and mammal; however, the role of teleost NAP1 in innate immunity remains unknown. In this paper, NAP1 homologue of black carp ( Mylopharyngodon piceus ) has been cloned and characterized. Black carp NAP1 (bcNAP1) migrated around 47 kDa in immunoblot assay and was identified as a cytosolic protein by immunofluorescent staining. bcNAP1 showed little IFN promoter-inducing ability in the reporter assay and bcNAP1 presented no antiviral activity against either grass carp reovirus (GCRV) or spring viremia of carp virus (SVCV) in the plaque assay. However, when co-expressed with black carp MDA5 (bcMDA5), bcNAP1 enhanced bcMDA5-mediated IFN promoter induction in the reporter assay. Accordingly, the plaque assay data demonstrated that the antiviral activity of bcMDA5 against both GCRV and SVCV was upregulated by bcNAP1. Additionally, the association between bcNAP1 and bcMDA5 has been identified through immunofluorescent staining and co-immunoprecipitation (co-IP) assay. Thus, the data generated in this study support the conclusion that bcNAP1 interacts with bcMDA5 and up-regulates bcMDA5-mediated antiviral signaling during host innate immune activation. Highlights: bcNAP1 interacts with bcMDA5. bcNAP1 enhances bcMDA5-mediated IFN promoter induction. The antiviral activity of bcMDA5 against both GCRV and SVCV is up-regulated by bcNAP1.